2016
DOI: 10.1371/journal.pone.0147617
|View full text |Cite
|
Sign up to set email alerts
|

The "Majority Illusion" in Social Networks

Abstract: Individual’s decisions, from what product to buy to whether to engage in risky behavior, often depend on the choices, behaviors, or states of other people. People, however, rarely have global knowledge of the states of others, but must estimate them from the local observations of their social contacts. Network structure can significantly distort individual’s local observations. Under some conditions, a state that is globally rare in a network may be dramatically over-represented in the local neighborhoods of m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
151
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(160 citation statements)
references
References 47 publications
5
151
0
4
Order By: Relevance
“…The study of these digital footprints has led to the emergence of computational social science, allowing to quantify at large-scales our political ideas and preferences [1], to discover roles in social networks [2,3], to predict our health [4] and personality [5], and to determine external effects on online behavior [6]. Importantly, in OSM, users are at the same time both actors and receivers and therefore the amplification of a trend originates from the interplay between influencing [7,8] and being influenced [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The study of these digital footprints has led to the emergence of computational social science, allowing to quantify at large-scales our political ideas and preferences [1], to discover roles in social networks [2,3], to predict our health [4] and personality [5], and to determine external effects on online behavior [6]. Importantly, in OSM, users are at the same time both actors and receivers and therefore the amplification of a trend originates from the interplay between influencing [7,8] and being influenced [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The images of ‘cloud chasing’ could contribute to the normalisation of vaping, characterising the act as harmless and fun, and more common and accepted than it actually is offline. 21 Research has consistently demonstrated the strong effect of peer influence and perceptions of peer norms on combustible cigarette use. 2223 However, tobacco education programmes have successfully combatted the effects of peer influence by addressing the associated social norms, 2425 a strategy that could be implemented on social media.…”
Section: Discussionmentioning
confidence: 99%
“…It should surely be each individual reader who independently judges the worth of that opinion and this individual should not be swayed by the popular and well connected person or group who posted it. Otherwise a dangerous or hateful opinion can spread so far that it becomes a ‘majority illusion’ (Lerman et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…It should surely be each individual reader who independently judges the worth of that opinion and this individual should not be swayed by the popular and well connected person or group who posted it. Otherwise a dangerous or hateful opinion can spread so far that it becomes a 'majority illusion' (Lerman et al, 2015). The type of natural selection of memes found in the swarm can be characterized as a non intentional selection process (Hull, 1988) in which the differential survival of alternative nest site propositions identifies the best competing alternatives.…”
Section: Discussionmentioning
confidence: 99%